Precisely controlling endogenous protein dosage in hPSCs and derivatives to model FOXG1 syndrome - Wenliang Zhu (Nature Portfolio, 2019)
Altered dosage of developmental regulators such as transcription factors can result in disorders, such as FOXG1 syndrome. Here, the authors demonstrate the utility of SMASh technology for modulating protein dosage by modeling FOXG1 syndrome using human pluripotent stem cell-derived neurons and neural organoids.